Cyclicality of SME lending and government involvement in banks - Patrick Behr; Daniel Foos; Lars Norden (Deutsche Bundesbank, 2015)
Recent regulatory efforts aim at lowering the cyclicality of bank lending because of its potential detrimental effects on financial stability and the real economy. We investigate the cyclicality of SME lending by local banks with vs. without a public mandate, controlling for location, size, loan maturity, funding structure, liquidity, profitability, and credit demand-side factors. The public mandate is set by local governments and stipulates a deviation from strict profit maximization and a sustainable provision of financial services to local customers. We find that banks with a public mandate are 25 percent less cyclical than other local banks. The result is credit supply-side driven and especially strong for savings banks with high liquidity and stable deposit funding. Our findings have implications for the banking structure, financial stability and the finance-growth nexus in a local context.
Keywords: G20; G21; 330; Banks; Loan growth; SME finance; Business cycles; Financial stability